2021
DOI: 10.2196/30010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing COVID-19 Vaccine Uptake and Effectiveness Through the North West London Vaccination Program: Retrospective Cohort Study

Abstract: Background On March 11, 2020, the World Health Organization declared SARS-CoV-2, causing COVID-19, as a pandemic. The UK mass vaccination program commenced on December 8, 2020, vaccinating groups of the population deemed to be most vulnerable to severe COVID-19 infection. Objective This study aims to assess the early vaccine administration coverage and outcome data across an integrated care system in North West London, leveraging a unique population-lev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 18 publications
4
39
0
1
Order By: Relevance
“…The chance of getting infection and having COVID-19 increases with age, so also the VE [ 27 , 28 ]. The participants in all the UK studies were comparatively older than our study except for the study reported from north-west London [ 26 ]. Lopez Bernal et al .…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…The chance of getting infection and having COVID-19 increases with age, so also the VE [ 27 , 28 ]. The participants in all the UK studies were comparatively older than our study except for the study reported from north-west London [ 26 ]. Lopez Bernal et al .…”
Section: Discussionmentioning
confidence: 89%
“…VIVALDI cohort study [25] which requited older adults (≥65 years) of UK as study participants reported 68% risk reduction (at 35 to 48 days) of contracting SARS-CoV-2 following single jab of Oxford-AstraZeneca vaccine. Even higher risk reduction of infection [74% (28 day onwards)] following single standard dose of Oxford-AstraZeneca vaccine was claimed by Glampson et al [26] which enrolled participants of all ages (≥16 years) in their study. Both these observations were higher compared to us.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations